Efektivitas Metode Penugasan melalui Aplikasi Whatsapp Terhadap Hasil Belajar Matematika Peserta Didik di Sekolah Dasar - lasyana kusumastuti; Arissona Dia Indah Sari; Iqnatia Alfiansyah (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2023)
Based on the results of interviews with teachers at SD Negeri 1 Tritunggal, a problem was found, namely the low learning outcomes of students in mathematics subjects, especially during the COVID-19 pandemic which required the implementation of online learning. This study aims to determine the effectiveness of the learning method on student learning outcomes at SD Negeri 1 Tritunggal. The type of research used in this research is descriptive quantitative. In this study, using the fourth grade students of SD Negeri 1 Tritunggal, totaling 14 children as research subjects. Data collection methods used are interviews and tests to determine student learning outcomes. Based on the results of data analysis from interviews and tests given, it is known that the assignment method through the WhatsApp application is not effective on the learning outcomes of fourth grade students of SD Negeri 1 Tritunggal in mathematics. This can be seen from the percentage of student learning completeness which is less than 75%, which is only 57.14% who complete.